The Effect of Food Security Programs Through Village Funds on the Income of Village Communities in Hamparan Perak District - Sitorus, Reyza Suwanto; Siregar, Aflahun Fadhly; Alqamari, Muhammad (JURNAL AGROPLASMA, 2024)
Food security is one of the development priorities within the framework of the government, food security programs through village funds are implemented to encourage rural communities to be able to be food independent, Fulfill their own household food so that it is expected to increase the income of rural communities. This study intends to see the effect of food security programs through village funds on the income of rural communities in Hamparan Perak sub-district. The data collection method used in this study is a multiple linear regression test which aims to determine the effect of the independent variable on the partially bound variable. From the original study, it was found that the verticulture variable has a sig value of 000 which means < 0.05 with a calculated T value of -13.877 which means > from T table 1.75305, it is concluded that Ha is accepted meaning that there is a significant influence between verticulture variables on income in the opposite or negative direction, hydroponic variables have a sig value of 0.047 which means < 0.05 with a calculated T value of 2.167 which means > from T table 1.75305 then it is concluded that Ha is accepted this means that there is a positive and significant influence between hydroponic variables on income, egg hatching variables have a GIS value of 000 which means < 0.05 with a calculated T value of 11.868 which means > from T table 1.75305 then it is concluded that Ha is accepted meaning that there is a positive and significant influence between egg hatching variables on income, livestock variable has a sig value of 000 which means < 0.05 with a calculated T value of 92.382 which means > from T table 1.75305, it is concluded that Ha is accepted meaning that there is a positive and significant influence between livestock variables on income. Keywords: village fund, food security, revenue